Output and price volatility spillovers among ECOWAS members: The role of global and regional uncertainties - Matthew A. Dada; Oluwatomisin J. Oyewole; Ismail O. Fasanya (Scientific African, 2023)
This paper examines the role of global and regional uncertainties on output and price dynamics connectedness between members of the Economic Community of West African States (ECOWAS) over the period of 1990 to 2020. The paper employs the Time-Varying Parameter Vector Autoregression connectedness framework to compute the spillover indexes and the non-parametric causality-in-quantile approach to analyze the causal effect of Global and Africa uncertainties on the output and price connectedness between the countries. Our findings indicate a high degree of interdependence between ECOWAS members in terms of output and prices with the exception of Togo and Mali which show the weakest vulnerability to idiosyncratic shocks from other West African countries. Also, the causal analysis provides evidence supporting a non-linear causal relationship between economic and trade uncertainties and the connectedness between ECOWAS economies, mostly at lower and median quantiles. Policymakers are advised to ensure stability in economic policies and rapid policy intervention to tackle economic crises to reduce economies' exposure to risks and speculative shocks.